Beauty and the Beast [videorecording (DVD)] (Walt Disney signature collection., 2017)
Be our guest at the enchanted 25th Anniversary celebration, universally acclaimed as one of Disney's finest animated features and now honored in the Walt Disney Signature Collection. Join brave, independent Belle on the adventure of a lifetime as she sets out to rescue her father and finds herself in the castle of a mysterious beast. This timeless tale overflows with unforgettable characters and Academy Award-winning music (Best Song, Best Score, 1991)!